Huruf Jar Ba dan Kandungan Maknanya dalam Q.S. Al-Maidah (The Letter Jar Ba and Its Meaning in Q.S. Al-Maidah) - Nur Asdaliah; Mukhtar Mukhtar; Hamzah Hamzah; Basri Mahmud; Mujahid Mujahid (Universitas Islam DDI AGH Abdurrahman Ambo Dalle Polewali Mandar, Sulawesi Barat, 2022)
Penelitian ini bertujuan untuk mengetahui dan memahami makna huruf jar Ba yang terdapat dalam al-Quran khususnya pada surah Al-Maidah. Penelitian ini termasuk kajian kepustakaan (library research) yaitu teknik pengumpulan datanya melalui studi telaah terhadap isi buku-buku, literatur, catatan atau artikel ilmiah yang ada Adapun hasil penelitian ini, terdapat huruf jar ba sebanyak 91 kali terulang dalam surah Al-Maidah, dengan 5 makna huruf jar yang dapat diklasifikasikan sebagai berikut: 1) Bermakna al-Isti’anah terdapat pada ayat ke 3 dan 45. 2) Bermakna al-Mushahabah terdapat pada ayat ke 8, 13, 16, 29 dan 36. 3) Bermakna sababiyah terdapat pada ayat ke 13, 18, 32, 44 dan 58. 4) Bermakna al-Qasam terdapat pada ayat ke 53, 106 dan 107. Dan 5) Bermakna al-Tab’idiyyah dan atau al-Ilshaq pada ayat ke 6. This research aims to find out and understand the meaning of the letter jar ba contained in the Quran, especially in the Surah Al-Maidah. This research is a library research, namely a data collection technique through a study of the contents of existing books, literature, notes or scientific articles. The results of this study, there is a jar letter ba as many as 91 times repeated in the surah Al-Maidah, with 5 meanings of the letter jar which can be classified as follows: 1) al-isti'anah is found in verses 3 and 45. 2) al-mushahabah is found in verses 8, 13, 16, 29 and 36. 3) sababiyah is found in verses 13, 18, 32, 44 and 58. 4) al-qasam is found in verses 53, 106 and 107. And 5) the meaning of al-tab'idiyyah and or al-ilshaq is found in verse 6.